2017
DOI: 10.4102/sajip.v43i0.1398
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcomes of meaningful work among school teachers

Abstract: Orientation: Quality education is dependent on the well-being, engagement, performance and retention of teachers. Meaningful work might affect these employee and organisational outcomes.Research purpose: The aim of this study was to investigate antecedents and outcomes of meaningful work among school teachers.Motivation for the study: Meaningful work underpins people’s motivation and affects their well-being and job satisfaction. Furthermore, it is a significant pathway to healthy and authentic organisations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 40 publications
5
78
2
2
Order By: Relevance
“…Results confirmed that despite narcissistic leaders’ need to have affirmative relationships with people (Braun, ), their behaviours may have negative consequences for their followers. As suggested in the literature, leaders’ actions may have a significant relationship with MW (Fouché et al, ; Rosso et al, ); in particular, we found a negative relationship between NL and MW, where the self‐interest and the lack of concern for others negatively interact with the meaning of the nursing profession, which is strongly characterized by taking care of others and by prosocial values (Wrzesniewski et al, ). Moreover, narcissistic leaders may be unable to support their followers in recognizing and valuing the meaning of their work.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Results confirmed that despite narcissistic leaders’ need to have affirmative relationships with people (Braun, ), their behaviours may have negative consequences for their followers. As suggested in the literature, leaders’ actions may have a significant relationship with MW (Fouché et al, ; Rosso et al, ); in particular, we found a negative relationship between NL and MW, where the self‐interest and the lack of concern for others negatively interact with the meaning of the nursing profession, which is strongly characterized by taking care of others and by prosocial values (Wrzesniewski et al, ). Moreover, narcissistic leaders may be unable to support their followers in recognizing and valuing the meaning of their work.…”
Section: Discussionsupporting
confidence: 69%
“…According to the job characteristics model, task significance, task identity and skill variety are the main antecedents of MW; to these dimensions, Bremner and Carrière () added autonomy. Among the main sources of MW, Rosso et al (, p. 95) indicate: “the self, other persons, the work context and spiritual life,” devoting a subsection specifically to leaders as being among the significant “others” who influence MW, while Fouché, Rothmann, and van der Vyver () list four factors that contribute to MW: “firstly, work is meaningful when there is a fit between individuals and the organisation's values and mission. Secondly, the nature of the task (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Independence and work-life balance had a significant impact on teachers' job performance [33]. Promoting perceptions of meaningful work might contribute to higher work engagement, better self-ratings of performance, and retention of teachers [40].…”
Section: Teachers' Work Performancementioning
confidence: 99%
“…Teaching profession is, the same as a calling, characterized by a sense of personal mission, purpose in life and service towards others while most of the working time is spent in interactions with others (Dobrow, 2004;Saraf & Murthy, 2016;Wrzesniewski et al, 1997). Moreover, teachers with the calling orientation are more enthusiastic towards their work (e.g., Buskist, Benson, & Sikorski, 2005), more satisfied with their job and life (Wrzesniewski et al, 1997), more caring for their students' well-being (Bullough & Hall-Kenyon, 2012), more engaged at work, perceiving their work as more meaningful, as a service for the greater good (Fouche, Rothmann, & van der Vyver, 2017;Rothmann & Hamukangandu, 2013a;Willemse & Deacon, 2015). Croatian elementary school teachers, who perceive teaching as a calling tend to be happier, more satisfied with their job and life, find more meaning in life, and have a lower level of emotional exhaustion (e.g., Jurčec, 2014;Jurčec & Rijavec, 2015).…”
Section: Calling Orientationmentioning
confidence: 99%